The effect of supine positioning on maternal hemodynamics during late pregnancy. (2nd December 2019) - Humphries, Aimee; Mirjalili, S. Ali; Tarr, Gregory P.; Thompson, John M. D.; Stone, Peter
Abstract: Introduction: Recent studies have demonstrated an association between maternal supine sleep position and an increased risk of late stillbirth. During late pregnancy, the gravid uterus compresses the inferior vena cava (IVC) when a woman lies in the supine position. The azygos system of veins is the dominant pathway of collateral venous return back to the heart in the event of acute obstruction of the IVC. It is suggested that this pathway provides adequate collateral venous circulation in the event of IVC compression in the supine position during late pregnancy. Objective: Investigate the effect of supine positioning on maternal hemodynamics during late pregnancy and the role of collateral venous circulation. Methods: Ethics approval was obtained and 12 women with singleton pregnancies between 35- and 38-week gestation underwent magnetic resonance imaging in the supine and left lateral decubitus positions using a Skyra 3T system (Siemens). Phase-contrast images were evaluated to measure cardiac output, blood flow through the azygos vein, and blood flow through the abdominal aorta (AA) and IVC at two levels: at the level of aortic bifurcation and immediately above the renal veins. Results: The supine position was associated with a 16.4% reduction in cardiac output when compared to the left lateral position. In addition, blood flow through the IVC decreased at its origin by 85.3% and by 44.4% at the level of the renal veins. Blood flow through the azygos vein increased in the supine position by 220%. Blood flow through the AA at the level of the renal veins did not differ significantly; however, it is reduced by 32.3% at the level of the aortic bifurcation. Conclusions: Women in late pregnancy experience an increase in collateral venous blood flow when lying supine, likely as a response to marked compression of the IVC in this position. However, cardiac output and aortic blood flow were found to decrease while in the supine position.